Viscosity data of al203/water and al2031 (eg/water) mixture nanofluids and the hysteresis phenomenon - Said, Z.; Sajid, M.H.; Alim, M.A.; Saidur, Rahman (2013)

(untitled)
The effects of temperature and low particle volume concentration on the dynamic visosity of the Ah03/water and Ah03lEG/water-based nanofluids are investigated. Measurements of the nanofluid viscositres were accomplished using Brookfield viscometer (DV-II + Pro Programmable Viscometer) with a tempera~re controlled bath, supplied by Brookfield engineering laboratories of Malaysia. Viscosity of the stud led nanofluids are strongly depended on the Ah03 particle volume fractions in the base fluid. Data were collected for temperatures ranging from 25 to 80°C. The presence of aggregated Ah03 nanoparticles in the fluid, with average diameter of 109nm, which is -8 times the primary diameter (13nm) of Ah03 nanoparticles, have been confirmed by Dynamic Light Scattering (DLS) data. The results clearly showed the presence of a critical temperature, beyond which the particle suspension properties were noticed to be radically changed, which result in activating the hysteresis phenomenon. The hysteresis phenomenon on viscosity measurement, which IS believed to be the first observed for EG/water-based nanofluids, has raised serious concerns regarding the use of nanofluids for heat transfer enhancement purposes.